Canned citrus processing techniques, equipment, and food safety - Shan, Yang (Academic Press, 2016)
"Canned Citrus Processing: Techniques, Equipment, and Food Safety comprehensively presents the technical and development trends of the canned citrus industry. This book provides solutions to typical problems of canned citrus manufacturing and processing; presents an overview of the canned citrus industry, introduces canned citrus processing machinery and equipment, and discusses the processing quality, safety control, and related standards"--Provided by publisher.